PERBANDINGAN HASIL HITUNG JUMLAH ERITROSIT MENGGUNAKAN TABUNG VACUTAINER EDTA BERDASARKAN SEBELUM DAN SESUDAH KADALUARSA 6 BULAN DAN 12 BULAN - Endra Topan; Pangesti, Ira; Puspodewi, Dini (Pharmaqueous: Jurnal Ilmiah Kefarmasian, 2025)
Erythrocytes or red blood cells are one of the components of blood that are dense shaped like a disc and do not have a nucleus with a size of 7-8 μm that is immobile, reddish-yellow and chewy so that it can change shape according to the blood vessels that are passed. If the blood collection vacutainer tube containing the anticoagulant is used past the expiration date, it is likely that the vacuum does not draw the required amount of blood, so the anticoagulant does not work effectively and does not prevent the blood from clotting it. Based on this background, the purpose of this study is to determine the comparison of the results of calculating the number of erythrocytes using edta vacutainer tubes based on before and after the expiration of 6 months and 12 months. The type of study is a descriptive analytical study by looking at whether there is a comparison of the results of calculating the number of erythrocytes using EDTA vacutainer tubes based on before and after the expiration of 6 months and 12 months with univariate and bivariate data collection and analysis techniques. Based on the results of statistical analysis, it can be seen that the average score of participants decreased from before the ED intervention (M = 4.559; SD = 0.310) to 4.453 (SD = 0.379) at 6 months after ED, and decreased again to 4.437 (SD = 0.438) at 12 months after ED. Despite this downward trend in mean values, the results of the Repeated Measures ANOVA test showed that this difference was not statistically significant (F(1.216) = 2.871; p = 0.086), although p was close to the significance threshold value (p < 0.05). This means that there was no significant change in the score between measurement times, either before or after the ED in the 6 and 12-month periods. Although statistical tests say there is no significant difference, checking the number of erythrocytes using vacutainer EDTA tubes before expiration is still recommended because descriptively there is an increase and decrease in the number of erythrocytes.